WORST OF ALL POSSIBLE WORLDS: DISENTANGLING FROM DYSTOPIAN SPACE AND DEHUMANIZATION IN ROY ARAGONS GANAGAN - Mark Louie Tabunan (International Journal of Humanity Studies (IJHS), 2021)
The war on drugs in the Philippines, despite President Dutertes rhetoric of saving the country, has killed alarming numbers of people. This article analyzes a dystopian text titled Ganagan (Fertilizer) by Roy Aragon which is about the Duterte administrations war on drugs. Deploying close reading and semiotics, it shows that the story portrays the punitive and vindictive nature of the war on drugs as a totalitarian project which resulted in dehumanization and collapse of human values. It further argues that the text suggests a possible future in which Dutertes utopian pursuit of the best of all possible worlds, which has done away with dangerous drugs, is driven less by the search for happiness than by a determined faith in justice. Lastly, the analysis focuses on the vegetable garden which Castaas, the main character, has cultivated. Launching off from Edward Sojas trialectics of spatiality and Thirdspace and conventions of dystopian fiction, the article shows that the garden is an ambivalent position, negotiation, and critique of the war on drugs. Hence, the garden, as a lived space, though imposing a desired order, could also be a site of disentanglements and resistance.